Non-canonical translation initiation of the spliced mRNA encoding the human T-cell leukemia virus type 1 basic leucine zipper protein. Issue 20 (12th September 2018) - Cáceres, C Joaquín; Angulo, Jenniffer; Lowy, Fernando; Contreras, Nataly; Walters, Beth; Olivares, Eduardo; Allouche, Delphine; Merviel, Anne; Pino, Karla; Sargueil, Bruno; Thompson, Sunnie R; López-Lastra, Marcelo
Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the etiological agent of adult T-cell leukemia (ATL). The HTLV-1 basic leucine zipper protein (HBZ) is expressed in all cases of ATL and is directly associated with virus pathogenicity. The two isoforms of the HBZ protein are synthesized from antisense messenger RNAs (mRNAs) that are either spliced ( sHBZ ) or unspliced ( usHBZ ) versions of the HBZ transcript. The sHBZ and usHBZ mRNAs have entirely different 5′untranslated regions (5′UTR) and are differentially expressed in cells, with the sHBZ protein being more abundant. Here, we show that differential expression of the HBZ isoforms is regulated at the translational level. Translation initiation of the usHBZ mRNA relies on a cap-dependent mechanism, while the sHBZ mRNA uses internal initiation. Based on the structural data for the sHBZ 5′UTR generated by SHAPE in combination with 5′ and 3′ deletion mutants, the minimal region harboring IRES activity was mapped to the 5′end of the sHBZ mRNA. In addition, the sHBZ IRES recruited the 40S ribosomal subunit upstream of the initiation codon, and IRES activity was found to be dependent on the ribosomal protein eS25 and eIF5A.